How to solve the systems by using the addition method or the substitution method.
Thank you for the opportunity to help you with your question!
Let us use substitution method
From (i) let us make x the subject of the formula as shown below
x = 1/3-1/6y -------------(iii)
Now substitute (iii) into (ii) for x as shown below
5(1/3-1/6y) + 2y=2
5/3-5/6y + 2y=2
-5/6y + 2y = 2-5/3
x = 1/3-1/6y
x = 1/3-1/6*2/7
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?